Covid-19 Pandemic and Institutional Reconstruction Towards a New Normal Life - Ricardi S Adnan (Indonesian Center for Religion and Society Studies (InTReSt), 2021)
New norms and social institutions have emerged in connection with the Covid-19 pandemic and in many ways have replaced the previously considered good order. The foreign phrase which is currently a term has been agreed upon by all parties as an invitation and a word of hope - new normal. Through literature study, this article reviews the fact that there have been institutional changes in various aspects of life because of the pandemic faced by the community for more than a year. By conducting a study of the results of research and internal monitoring of the Covid-19 Task Force and supported by secondary data, this article discusses three levels of social interaction structure that are interconnected and influence each other. At first the pandemic brought shocks that caused negative effects on almost all aspects of life, but in the course of time the difficult conditions gave various optimism to rearrange existing institutions to be more relevant to the contemporary context full of change. Doubts, incoherence, and weak aspects of government institutions are the cause of the continued spread of the pandemic. The legitimacy of the policy is the key to stopping the pandemic as well as institutional restructuring.